Creating a culture of children's rights in the perspective of the preventive education of Fr. John Bosco - Stanisław Chrobak (Studia z Teorii Wychowania)
Educational activity of the Rev. Jan Bosko (1815-1888) and his preventive system began in the ‘40s XIX century. Currently, this educational work is continued by the Salesian Family and attracts the interest and enjoys the recognition of teachers and educators in 132 countries. In his multidirectional preventive action for the youth, the Rev. Bosko supported human, cultural, professional and religious formation, providing care, assisting, promoting a new quality of life. Education/upbringing in this context aims to create a culture of human rights/children's right, capable of dialoguing, persuading and eventually preventing the violation of these rights. In this perspective, the aim of the article is to reveal the immanent values the preventive system of the Rev. J. Bosko, facilitating the creation of a preventive culture of human rights/children's right, which should be multidimensional and integral and constitute a platform of dialogue for a new culture of rights and solidarity.